Positive follow-up blood cultures identify high mortality risk among patients with Gram-negative bacteraemia. (July 2020) - Maskarinec, S.A.; Park, L.P.; Ruffin, F.; Turner, N.A.; Patel, N.; Eichenberger, E.M.; van Duin, D.; Lodise, T.; Fowler, V.G.; Thaden, J.T.
Abstract: Objectives: The role of follow-up blood cultures (FUBCs) in the management of Gram-negative bacteraemia (GNB) is poorly understood. We aimed to determine the utility of FUBCs in identifying patients with increased mortality risk. Methods: An observational study with a prospectively enrolled cohort of adult inpatients with GNB was conducted at Duke University Health System from 2002 to 2015. FUBCs were defined as blood cultures performed from 24 hours to 7 days from initial positive blood culture. Results: Among 1702 patients with GNB, 1164 (68%) had FUBCs performed. When performed, FUBCs were positive in 20% (228/1113) of cases. FUBC acquisition was associated with lower all-cause in-hospital mortality (108/538, 20%, vs. 176/1164, 15%; p 0.01) and attributable in-hospital mortality (78/538, 15%, vs. 98/1164, 8%; p < 0.0001). Propensity score–weighted Cox proportional hazards models revealed that obtaining FUBCs was associated with reductions in all-cause (hazard ratio (HR) 0.629; 95% confidence interval (CI), 0.511–0.772; p < 0.0001) and attributable mortality (HR 0.628; 95% CI, 0.480–0.820; p 0.0007). Positive FUBCs were associated with increased all-cause mortality (49/228, 21%, vs. 110/885, 11%; p 0.0005) and attributable mortality (27/228, 12%, vs. 61/885, 7%; p 0.01) relative to negative FUBCs. Propensity score–weighted Cox proportional hazards models revealed that positive FUBCs were associated with increased all-cause (HR 2.099; 95% CI, 1.567–2.811; p < 0.0001) and attributable mortality (HR 1.800; 95% CI, 1.245–2.603; p 0.002). In a calibration analysis, a scoring system accurately identified patients at high risk of positive FUBCs. Conclusions: Rates of positive FUBCs were high and identified patients at increased risk for mortality. Clinical variables can identify patients at high risk for positive FUBCs. FUBCs should be considered in the management of GNB.